Phytochemical Screening of Aqueous, Acetone, Ethanol and Methanol Leaf Extracts of Ocimum teniflorum, Ocimum gratissimum and Ocimum sanctum - Kavyamala, D.; Jayamma, P.; Rani, N. Usha; Babu, M. Mahesh (International Journal of Economic Plants, 2023)
The experiment was carried out during November, 2019 to July, 2020 at Department of Food Safety and Quality Assurance, College of Food Science and Technology, Pulivendula, ANGRAU, Andhra Pradesh, India. A large number of plants show enormous versatility in synthesizing complex materials which have no immediate obvious effect on growth or metabolic functions. Phytochemicals are naturally occurring and biologically active components that have potential disease inhibiting capabilities. Phytochemicals are effective in combating or preventing disease due to their antioxidant effect. The most important of these phytochemicals are alkaloids, tannins, flavonoids, saponins and phenolic compounds. Ocimum is a well-known medicinal plant that consists of various biochemically active components which have many functional effects. The leaf extracts were prepared by using aqueous, acetone, ethanol and methanol solvents and phytochemical analysis was conducted for tannins, saponins, phlabotannins, flavonoids, terpenoids, glycosides and steroids. The results revealed that tannins were found in all the extracts of three Ocimum spp., Saponins were present in all extracts except methanol extract of Ocimum spp., the presence of phlabotannins were observed only in aqueous extract Ocimum spp., Flavonoids were present in aqueous and methanol extracts of Ocimum spp., Glycosides were found in ethanol and methanol extracts of Ocimum spp., The presence of steroids was observed in all extracts except aqueous of Ocimum spp., Terpinoids were present in all extracts except aqueous extract of O. teniflorum and O. gratissimum.